Factors Influencing Incomplete Chemotherapy in Breast Cancer - Jearwattanakanok, Kijja (Journal of Health Science of Thailand, 2017)
Breast cancer is the second most common cancer inThailand. Chemotherapy has an important role in treatment of breast cancer. However, complications and side effects from chemotherapy may contribute to incompleteness in treatment. The objective of this retrospective analytic study was to identify factors influencing incomplete chemotherapy in Nakornping hospital. A retrospective analytic study by a review and analysis of medical records of 171 breast cancer patients receiving chemotherapy during 2003-2006 was conducted. Data were analyzed to identify relation between incomplete chemotherapy and age, distance between patient house and the hospital, cancer stage, type of administration (adjuvant or neoadjuvant), drug regimens, menopause, leukopenia, and other complication. It was found that only different age groups, menopause status, and TMN staging were factors influencing complete chemotherapy. Younger patients, premenopause, and early stage were likely to receive complete chemotherapy.